Law Enforcement Against Transfer of Objects Fiduciary in Kudus Police - Agus Budianto; Umar Ma’ruf (Jurnal Daulat Hukum, 2019)
The purpose is achieved in this research are: to know the mechanism of the occurrence of a credit agreement in the German Fiducia between Guarantees the lender with the leasing in the state law enforcement to know Grail in the event of a transfer of the object of the fiduciary guarantee in the region Police Resort of Kudus. To know the constraints in the legal enforcement of the related existence of a Fiduciary guarantee redirects object at Police Resort, and the solution for consumers.This research is the legal research approach or using Empirical Juridical also called as the Juridical Sociological. This research is descriptive analytical research as specified.Research results in the agreement between the creditors and the debtor financing mutual committing yourself, before making the deal, leasing the breathtaking debtor must meet the obligation to pay installments on a timely basis in accordance with the quantity and the date of the has been agreed, then release the rights and obligations not to a make problem. In terms of collateral object is the object of fiduciary transferred to third parties apply the principle creditors can still execute the collateral objects. The transfer of objects into objects fiduciary third parties does not preclude the right of creditors to keep executing the fiduciary guarantee object.The conclusions in this study is on the implementation of the Business Funding and need the assistance of the police dai it will be very easy and possible to overcome the rogue debtor.Keyword: Law Enforcement; The Transfer Object Fiduciary Guarantee; Fiduciary; Police Resort of Kudus